Career Interest and Self-Efficacy Beliefs of the Senior High School Students and their Relationship with their Academic Performance - Mallari, Camille Joy; Guevara, Maria Isabel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between career interests, self-efficacy beliefs, and academic performance among 111 Grade 12 students from the pioneer Senior High School batch at Central Luzon College of Science and Technology during School Year 2017–2018. Anchored on Social Cognitive Career Theory and Holland’s RIASEC framework, the study investigated whether career interests and self-efficacy beliefs significantly relate to students’ grade point averages (GPA) within a Maritime-oriented educational context. The study utilized a descriptive-correlational research design employing total population sampling. Data were collected using the O*NET Interest Profiler and the General Self-Efficacy Scale (GSE), while academic performance was measured through respondents’ GPA obtained from official school records. Descriptive statistics and Pearson Product-Moment Correlation Coefficient (r) were used to analyze the data. Findings revealed that most respondents demonstrated low career interest across the six RIASEC dimensions but showed moderate levels of action, coping, and general self-efficacy beliefs. Academic performance across tracks was generally satisfactory to very satisfactory. Among the six career interest dimensions, only investigative interest showed a statistically significant but very weak positive relationship with GPA. Action, coping, and general self-efficacy beliefs were not significantly related to academic performance. The findings suggest that career interests and self-efficacy beliefs alone may have limited predictive value for academic intervention programs and emphasize the importance of integrating psychological, environmental, and academic support factors in student development initiatives. The study supports SDG 4 – Quality Education by contributing evidence for improved academic advising and career guidance programs. It also aligns with SDG 8 – Decent Work and Economic Growth and SDG 9 – Industry, Innovation and Infrastructure through its focus on career preparation and Maritime education. The study contributes to educational, socio-economic, and institutional sustainability by supporting evidence-based student guidance and academic intervention practices.
Keywords: Academic Performance; Career Interests; Coping Self-Efficacy; Grade Point Average; Maritime Education; RIASEC; Senior High School Students; Social Cognitive Career Theory; Vocational Guidance